Peran Aktor Eksternal Dalam Pengembangan Pariwisata Di Desa Wisata Samiran Kecamatan Selo, Kabupaten Boyolali - Nurkhayani, Dewi; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i01.p17, 2018)
This research was to analyze The Role of External Agent to Tourism Development of Samiran Tourism Village. Samiran Tourism Village become mainstay tourism attraction at Boyolali Regency. Samiran Tourism Village have natural potential namely Merapi mountain dan Merbabu, Samiran Tourism Village is located on slope of the mountain. The development of Samiran Tourism Village is so rapid, as evidenced by the achievement that 3rd national champion in prestigious event of Tourism Village Competition held by the Ministry of Tourism and Creative Economy. The successfull of Samiran Tourism Village today, because of the high participation of local communities. But, who would have thought tucked into role of external agent in the development. The external agent to become a director in the development of Samiran Tourism Village. This research conducted using qualitative methods, described through descriptive teqniques, data were collected through observation and depth interview on the informant. Selection of informant invitation purposive sampling technique. This study shows the role of external agent as a drafter, the mouthpiece in the information and tourism ambassador in the tourism development at the Samiran Tourism Village. Existing barriers be addressed to the quite and preferably local communities, especially younger generation must be learh how to be independent tourism area, in order to avoid dependency on external agent.   Keywords : Role, External Agent, Rural Tourism, Tourism Village